LA GESTIÓN DEL PROCESO DE AUTOEVALUACIÓN Y LA AUTORREGULACIÓN PARA LA ACREDITACIÓN DE LA CARRERA DE TRABAJO SOCIAL: 1998-2000 - Ruiz, Ana Isabel (2001)
This article is about the procedure followed in the process of self-evolution and self-regulation for accreditation, developed by the school of Social Works, between 1998 and the year 2000. Interpretation and self-criticism of the works done is included in this article as a contribution to this topic.